2020
DOI: 10.1186/s12879-020-05652-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-toxigenic Corynebacterium diphtheriae infective endocarditis with embolic events: a case report

Abstract: Background Corynebacterium diphtheriae (C. diphtheriae) infections, usually related to upper airways involvement, could be highly invasive. Especially in developing countries, non-toxigenic C. diphtheriae strains are now emerging as cause of invasive disease like endocarditis. The present case stands out for reinforcing the high virulence of this pathogen, demonstrated by the multiple systemic embolism and severe valve deterioration. It also emphasizes the importance of a coordinated interdisciplinary work to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
(20 reference statements)
0
5
0
2
Order By: Relevance
“…Similar cases of bacteremia and significant clinical sequelae resulting from non-toxigenic diphtheria are rare ( 28 ). In developed countries, such cases are even rarer and typically present in patients with an immunocompromised condition, such as those with a history of IV drug use ( 29 , 30 ). Our patient had no known pre-existing conditions (immunological or otherwise), was established with preventative, outpatient care, and had no incidental diagnosis despite prior hospitalization and work up by specialists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar cases of bacteremia and significant clinical sequelae resulting from non-toxigenic diphtheria are rare ( 28 ). In developed countries, such cases are even rarer and typically present in patients with an immunocompromised condition, such as those with a history of IV drug use ( 29 , 30 ). Our patient had no known pre-existing conditions (immunological or otherwise), was established with preventative, outpatient care, and had no incidental diagnosis despite prior hospitalization and work up by specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiogenic toxicity due systemic infection with C. diphtheria is uncommon in developed countries ( 31 ). Such cases resulting from non-toxin producing strains are rare, even outside of the U.S. ( 30 ). These factors taken together make the case unusual.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined whether the negative tox gene is – like in C. belfantii – a constant feature in this species, which might directly influence its role as a human diphtheria pathogen. On the other hand, even severe human infections with non-toxigenic strains must not be underestimated with respect to the pathogenic potential (de Santis et al 2020 ; Massmann et al 2020 ). With four more animal isolates from three dogs from this study and one fox (Sing et al 2016 ) and possibly also from two cat isolates from the USA (Hall et al 2010 ) it is tempting to speculate and remains to be determined whether C. rouxii is also a zoonotic pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the toxin is considered the major virulence factor in C. diphtheriae, in recent years several other virulence factors have been identified that act independently of the toxin [6][7][8][9][10][11][12][13][14]. Indeed, an increasing number of systemic infections caused by non-toxigenic C. diphtheriae strains, such as endocarditis, septic arthritis and osteomyelitis, have been reported across the globe [8,[15][16][17][18][19]. Furthermore, a growing number of Corynebacterium species have been reported to cause opportunistic infection [20][21][22][23][24], or disease in animals [25], with at least 67 species being of clinical or veterinary importance [26].…”
Section: Introductionmentioning
confidence: 99%